Software Development for Fluid-Flow Visualization Using Computer Graphics and Animation Technique - Liongson, Leonardo Q. (Philippine Engineering Journal; Vol 14 No 1 (1993), 2021)
This paper presents the principal results of a two-year software development project for the visualization of fluid motion using computer graphics and animation techniques. Twenty-five (25) visualization programs have been developed for potential flows, viscous flows, flows with heat and mass transfer, geostrophic flows, and open-channel flows. Single-page and double-page animation, and palette rotation (neon-light effect), featuring on the monitor screen the display of both text and graphics with color, animation, and sound, are the essential techniques utilized. Classical tools in engineering mathematics were numerically applied and implemented, such as complex variable theory, conformal mapping, both analytical and numerical solutions of ordinary and partial differential equations, and stochastic or random-walk simulation of the diffusion process.  The applied techniques (computer graphics, animation, analytical and numerical methods in engineering mathematics) exhibited varying degrees of performance in terms of a meaningful perception of fluid motion, depending on appropriateness of the application to certain types of flows and on the nature and amount of detail present in the images. With the added features of a simple and guided input menu, a facility for instant replay, and a real-time mode of computation and display, the programs serve as interactive teaching tools in fluid machines. (A Professorial Chair Lecture delivered on 21 June 1993 at the National Hydraulic Research Center, MH 233- A, College of Engineering, University of the Philippines, DIliman, Quezon City)